(untitled) (Світ фінансів, 2017)
Кириленко О. П., Бучковська Я. Г. Пріоритетні напрямки вдосконалення фінансування дошкільної освіти в Україні. Визначено найважливіші напрямки оптимізації фінансування дошкільної освіти в Україні. Обґрунтовано доцільність розвитку джерел фінансування дошкільної освіти, важливість застосування співфінансування у цій сфері, використання альтернативних шляхів надання послуг дошкільної освіти за рахунок коштів бюджету. Досліджено напрямки удосконалення міжбюджетних відносин з метою поліпшення фінансування дошкільної освіти. Kyrylenko O., Buchkovska Ja. Priority directions of perfection of preschool education financing in Ukraine. Major directions of perfection of preschod education financing are certain. Expediency of development of sourcing of preschod education is grounded, importance of application co-financing in the field, use alternative ways of services preschol education accound of budget. Directions of improvement of interbudgetary relationships are investigated with the aim of improvement of preschool education financing.